Genres of ‘Ilm al-Badī’ in Sūra al-Najm - Al Rashidi, Muhammad Ayub (Journal of Islamic and Religious Studies, 2016)
Arabic rhetorical sciences are: ‘Ilma al-Maani’ “the study of mening” ‘Ilma al-bayyan’ “the study of elucidation” and ‘Ilam al-Badi’ “the study of wondrous. This article describes two important phenomenon of Ilmi al-Badi known as ‘arravai al-lafzia’ “beauty of words” and ‘arravai al-manaviya’ “beauty of meaning” in Surah al Najam of the Holy Quran. Both these phenomenon are effectives rhetoric devices used in literature to eloquently convey the indent of words and meaning in this chapter. It is important to pondor more carefully about these phenomenon ، in order to uncover even more of the fascinating secret and beauties contained in God’s words and to enable man to imbibe from the limitless oceans of God’s knowledge to the extent of his own capacity.